Enhancement of Ca(2+)‐dependent Endonuclease Activity in L1210 Cells during Apoptosis Induced by 1‐β‐D‐Arabinofuranosylcytosine: Possible Involvement of Activating Factor(s) - Takauji, Rumiko (Jpn J Cancer Res, 1995)
Internucleosomal DNA fragmentation and morphological changes in nuclei typical of apoptosis were observed in L1210 cells incubated with 1.0 μg/ml of 1‐β‐D‐arabinofuranosylcytosine (ara‐C). To investigate the mechanisms involved, we examined the activities of endogenous endonucleases in nuclei and cytoplasm. Both fractions of control cells contained Ca(2+) ‐dependent endonuclease which was capable of mediating internucleosomal DNA fragmentation. The assay system using two kinds of target substrates, i.e., nuclear chromatin of CCRF‐CEM cells and naked DNA purified from the same cells, revealed that the activity of Ca(2+)‐dependent endonuclease was enhanced in the crude nuclear extracts of cells treated with 1.0 μg/ml of ara‐C for 24 h or 48 h. The activity was extracted more easily from ara‐C‐treated cells than control cells without sonication of the nuclear fraction. On the other hand, in the cytoplasmic fraction of the cells, the activity towards naked DNA was unchanged, whereas that towards nuclear chromatin was clearly enhanced. These results suggest that internucleosomal DNA fragmentation induced by ara‐C treatment is associated with enhancement and activation of constitutively expressed Ca(2+) ‐dependent endonuclease in L1210 cells.